Trabalho livre e escravidão em Atenas: o contraponto de Ellen Meiksins Wood ao viés antidemocrático dos clássicos Sócrates, Platão e Aristóteles - Lacowicz, Ellis Fernanda (2018)
This work aims to analyze the perspective of the researcher and historian Ellen Meiksins Wood (1942-2016) on Athenian democracy considering it a counterpoint to the antidemocratic view of the classical philosophers Socrates, Plato and Aristotle. The author presents his perspective in the books Democracia contra capitalismo (2011b) and Peasant-citizen and Slave: The Foundations of Athenian Democracy (1989). This books emphasize the figure of the free worker, especially the peasant-citizen, who had, according to Wood, an unprecedented juridical and political status, he was free from any kind of exploration by means of coercion, by either the landowners or the State. The traditional view was influenced by what Ellen Wood calls the myth of the idle mob, which claims that the citizens were an idle mob that could participate in political decisions because slaves would work in their place and because they were supported by public payments; the ones who inspired the myth were the Greek philosophers Socrates, Plato and Aristotle. In the first chapter, we discuss the traditional vision on the Athenian democracy. In the second chapter, the focus is on the participation of the peasant-citizen in the Athenian democracy, by the perspective of Ellen Meiksins Wood. Finally, in the third chapter, we discuss the author's method to study classical political theorists and their application in the works of Greek philosophers, since the method that the author used would have enabled this different view on the subject. The researcher says that the citizen status of the free worker and the anti-democratic will inspired by a vision on that condition are present in the political and cultural traditions of the Classical antiquity, which reached our time. Because, when the work class demanded participation in the new emerging democracies, — in England and in the United States, mainly — it was tried to reason that this participation would have to be restraint, to not put in risk the own existence of the democracy. This argument could be found in the texts of philosophers such as Plato, Socrates and Aristotle; this position was usually mobilized by the “authority” that those political classics enjoyed through a “textualist” reading. Nonetheless. Ellen Wood was able to show that perspective was a “bias” and it was not a matter of direct description of some pretense political reality of the Athenian democracy. Through the social contextualization of the political philosophers, it was possible to understand their positions as partisan – antidemocratic -, in the social and political conflict of the time those “classics” developed their political theories.